X-Ray Fluorescence Analysis as a Tool of Monitoring Soil Pollution Around The Central Geological Laboratory - Ts, Dagii; B, Davaasuren; N, Baljinnyam; Ts, Nadmid (Scientific transaction of the National University of Mongolia. Physics, 2022)
Heavy metal contamination of soil is a major concern from an ecological point of view. This study aims to characterize soil samples from different sites in the Central Geological Laboratory (CGL)’s area and to study heavy metal contamination in the environment. In this work Wavelength dispersive X-ray fluorescence spectrometry has been used to evaluate the heavy metals and some toxic elements pollution in the CGL area.